Hesitant heroes : private inhibition, cultural crisis - Ziolkowski, Theodore (Cornell University Press, 2004)
"Why, Theodore Ziolkowski wonders, does Western literature abound with figures who experience a crucial moment of uncertainty in their actions? In this highly original and engaging work, he explores the significance of these unlikely heroes for literature and history." "From Aeneas - who wavered momentarily before plunging his sword into Turnus's chest - to Hamlet, Orestes, Parzival, Wallenstein, and others, including Kafka's Josef K., Ziolkowski demonstrates that characters' private uncertainty reveals a classic opposition of binary forces."--Jacket